The Intersection and Divergence of New Urbanism and Environmental Psychology: An Exploration - Alexander, Don; Wydeman, Bronwyn (Frontiers in Built Environment, 2020)
Using the limited literature comparing the findings of New Urbanism and environmental psychology as to the desirable characteristics of neighborhoods and resident satisfaction, and with a focus on an urban inner-city neighborhood in Vancouver (Canada) built in the mid- and late-1970s, this paper focuses on the similarities and differences of the two orientations to the built environment, their respective strengths and weaknesses, and what each can learn from the other. It suggests that the planners and architects who planned and designed the neighborhood had an advanced grasp of community-building principles that are still relevant today, and New Urbanism and environmental psychology have much to learn from them and from each other.